Social Determinants of Neonatal Health Outcomes in Indonesia: A Multilevel Regression Analysis - Soeharno, Rooswanti; Sjaaf, Amal Chalik (UI Scholars Hub, 2024)
Indonesia’s neonatal mortality rate remains alarmingly high. This study addressed the determinants of neonatal outcomes in Indonesia, including the effects of a decentralized health system, socioeconomic disparities, and geographic variations. The analysis used 2018 national survey data across 34 provinces, 513 cities/districts, and 300,000 households, with a sample of 73,864 women aged 10-54 years who have given birth in the preceding five years. The multilevel regression was used to assess the impact of social determinants and systemic inequalities on neonatal health. Key findings revealed a neonatal mortality rate that, despite being preventable in many cases, remained high with significant disparities. The final model, incorporating individual and community-level factors, reduced unexplained variance by 28% (PCV), with community factors explaining 16% of the variability (ICC 0.1600). The community-level risk variability also decreased, as shown by a reduction in the Median Odds Ratio from 2.43 to 2.13. These results highlighted the importance of targeting individual and community factors to reduce the risk of babies being born at risk. There is a critical need for targeted health policies and local-specific interventions to bridge the equity gap and improve neonatal health outcomes.